Effects of Dietary Vitamin E Supplementation on Reproductive Performance, Egg Characteristics, Antioxidant Capacity, and Immune Status in Breeding Geese during the Late Laying Period - Zhenming Fu; Tao Zhong; Xiaoli Wan; Lei Xu; Haiming Yang; Houming Han; Zhiyue Wang (MDPI AG, 2022)
This study aimed to tentatively evaluate the effects of dietary vitamin E (VE) on goose reproductive physiology through the investigation of reproductive performance, egg characteristics, antioxidant capacity, and immune status in breeding geese. A total of 480 female and 96 male Jiangnan White breeding geese were randomly assigned to four treatments with four replicates, and each replicate had 30 females and six males. Four levels of VE were successively added to four treatment diets from 48 to 54 weeks of age, representing the effects of VE deficiency (0 IU/kg), basic-dose VE (40 IU/kg), middle-dose VE (200 IU/kg), and high-dose VE (2000 IU/kg). Neither the egg-laying rate nor the healthy-gosling rate were affected by any of the VE supplementations (p > 0.05). The qualified egg rate, hatchability of fertilized eggs, and spleen index were increased by each VE supplementation (p < 0.05). Egg fertility, the concentration of plasma reproductive hormones (i.e., the follicle-stimulating hormone, estradiol, and progesterone), follicular development, and antioxidant enzyme activities-i.e., the concentration of malondialdehyde (MDA), total antioxidant capacity (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px)-in the liver and ovary were improved by 200 IU/kg of dietary VE (p < 0.05). Plasma VE concentration, immunoglobulin A, and immunoglobulin G content were increased, whereas plasma vitamin D3 concentration was reduced by increasing dietary VE levels to 2000 IU/kg (p < 0.05). The VE deposition of yolk, the yolk color depth, and the albumen rate were increased by each VE supplementation (p < 0.05). Antioxidant enzyme activities (i.e., MDA concentration, T-AOC, SOD, and GSH) in yolk were improved by 200 IU/kg and 2000 IU/kg of dietary VE (p < 0.05), compared with 0 IU/kg. The VE deposition was significantly correlated with GSH activity and the MDA concentration in egg yolk (p < 0.05). However, the high intake of dietary VE (2000 IU/kg vs. 200 IU/kg) decreased egg fertility (p < 0.05) and reduced the antioxidant capacity in the liver and ovary (p < 0.05). The qualified egg rate was positively correlated to immunoglobulin production (p < 0.05). Egg fertility and hatchability were correlatively improved by increased antioxidant enzyme activity; decreased MDA in the liver and ovary; hatchability; and enhanced immune status (p < 0.05). To sum up, both VE deficiency and high-dose VE (2000 IU/kg) reduced reproductive performance, whereas a dose of 200 IU/kg VE achieved optimal fertility, possibly through enhancing antioxidant capacity and immune status.